Manufacturing method of composite high-resilience heat-conducting gasket
By adopting the composite high-resistance thermal conductivity method in the thermal conductivity gasket, and using the combination of fiber modified liquid and slurry, the problem of the reduction in the elasticity of the thermal conductivity gasket is solved, and the coordinated improvement of high thermal conductivity and high rebound rate is achieved.
Patent Information
- Application Number
- CN202411956296.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-28
- Publication Date
- 2025-03-25
AI Technical Summary
When the thermal conductivity coefficient of existing thermal gaskets reaches 6w/(m·k) or above, the elasticity of the existing thermal gaskets is greatly reduced, and the dimensional stability depends on viscosity. After long-term aging, the viscosity is lost, resulting in interface disconnection and system failure.
By using the method of producing composite high-resistance thermal conductivity gasket, the fiber modification liquid and slurry are prepared, coated on elastic fabric fibers, and heated and cured in a pretension state to form a material with high thermal conductivity and rebound rate.
It significantly improves the rebound rate and thermal conductivity of the thermal gasket, reduces dependence on resin, improves powder filling rate, reduces cost, and enhances the overall structural stability and reliability of the material.
Smart Images

Figure BDA0005215930470000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of thermally conductive gaskets, and in particular to a method for manufacturing a composite high-resilience thermally conductive gasket. Background Art
[0002] Thermally conductive silicone gaskets are widely used in the field of heat dissipation and heat conduction of electronic products due to their good surface wettability, elasticity and thermal conductivity. By filling the gap between the heating element and the heat dissipation component, it can effectively reduce the thermal resistance of the system and provide guarantee for the long-term stable operation of the equipment.
[0003] However, with the current trend of thermally conductive gaskets pursuing high thermal conductivity, when the thermal conductivity of the thermally conductive gasket reaches 6w / (m·k) and above, the filling rate of its thermally conductive powder often exceeds 95%. Since the proportion of silicone resin is too low, it is impossible to form an effective continuous phase, which leads to a significant decrease in the resilience of the thermally conductive gasket and almost zero residual stress after compression. In this case, the dimensional stability of the gasket is mainly maintained by viscosity. However, after long-term aging, the viscosity of the gasket will gradually be lost, and the hardness will continue to increase. Once affected by vibration or thermal expansion and contraction, interface detachment is likely to occur, which will cause the entire system to fail, so it needs to be improved. Summary of the invention
[0004] In order to improve the resilience of a thermally conductive gasket, the present application provides a method for manufacturing a composite high-resilience thermally conductive gasket.
[0005] The present application provides a method for manufacturing a composite high-resilience thermally conductive gasket using the following technical solution: A method for manufacturing a composite high-resilience thermally conductive gasket comprises the following steps: (1) preparing a fiber modification liquid, coating the fiber modification liquid on elastic fabric fibers, and obtaining modified fabric fibers after impregnation; (2) drying the modified fabric fiber and cutting it to obtain pretreated fabric fiber; (4) mixing alumina, vinyl silicone oil, hydrogen-containing silicone oil, a catalyst and an inhibitor to obtain a slurry; (5) pre-tensioning the pretreated fabric fiber to make the surface wrinkle-free to obtain pre-tensioned fabric fiber, coating the slurry on one surface of the pre-tensioned fabric fiber, heating and curing, coating the slurry on the other surface of the pre-tensioned fabric fiber, heating and curing to obtain a semi-finished product; (5) removing excess fabric from the tensioning edge of the semi-finished product to obtain a composite high-resilience thermal conductive gasket.
[0006] The fiber modification liquid can penetrate into the interior of the fiber, optimize the surface properties of the fiber, and enhance its bonding with the subsequent coating slurry, thus laying the foundation for improving thermal conductivity and resilience; high thermal conductivity alumina is mixed with silicone oil to form a slurry, so that the high thermal conductivity of alumina can be fully utilized, thereby improving the overall thermal conductivity of the material; at the same time, the slurry is coated on both sides of the pre-tensioned fabric fiber and heated and cured, so that the fabric fiber is fully wrapped and fixed by the slurry in the tensioned state. After being compressed by external force, this structure can quickly return to its original state by relying on the elasticity of the fiber and the elastic recovery force of the cross-linked structure in the slurry, thereby improving the resilience of the thermal conductive gasket.
[0007] The high rebound effect is achieved by utilizing the characteristics of elastic fabric. When subjected to pressure in the Z direction, the prefabricated fabric will undergo elastic deformation. Once the external force is removed, it can quickly return to its original shape, greatly reducing the dependence on resin. Under the premise of ensuring the same rebound level, the resin weight ratio can be significantly reduced, which in turn greatly increases the powder filling rate of the high rebound thermal gasket, thereby improving thermal conductivity and rebound ability and reducing costs.
[0008] Preferably, the fiber modification liquid includes hydrogenated silicone oil and naphtha.
[0009] Hydrogenated silicone oil has active silicon-hydrogen bonds, which can react chemically with the active groups on the surface of elastic fabric fibers to form chemical bonds, thereby chemically modifying the fiber surface and enhancing the compatibility and adhesion between the fiber and the subsequent coating slurry; naphtha can help the hydrogenated silicone oil to better disperse and penetrate into the internal structure of the fiber, so that the hydrogenated silicone oil is evenly distributed on the fiber surface to ensure the consistency of the modification effect; this uniform and effective modification allows the fiber to better cooperate with the slurry in the subsequent processing process. In terms of improving the thermal conductivity of the thermal conductive gasket, the modified fiber can conduct heat more effectively and promote the transfer of heat inside the gasket; due to the close combination of the fiber and the slurry and the optimization of the fiber's own performance, when the gasket is compressed by external force, the fiber can more effectively support and assist the material to return to its original shape, thereby significantly improving the comprehensive performance of the composite high-resilience thermal conductive gasket, so that it can better meet the needs of heat dissipation and elastic recovery in practical applications.
[0010] Preferably, the hydrogen-containing silicone oil accounts for 3-8% of the total mass of the fiber modification liquid.
[0011] The fiber modification liquid prepared according to the above mass ratio has good wettability and can effectively improve the compatibility and resilience of the modified fabric fiber and the slurry.
[0012] Preferably, the elastic fabric fibers include spandex fibers.
[0013] Spandex fiber has excellent elastic recovery properties. Its molecular chain structure contains flexible segments and rigid segments. When stretched by external force, the flexible segments can stretch freely, while the rigid segments support and limit excessive deformation. When the external force is removed, the molecular chains quickly shrink to restore the fiber to its original state. After being treated with fiber modification liquid, coated with slurry and subsequent processing steps, the spandex fiber can still maintain its high elasticity, providing a good rebound foundation for the thermal gasket. At the same time, spandex fiber has a certain heat resistance and will not experience serious performance degradation during the heating and curing process. It can be stably combined with other materials to ensure that the thermal gasket can maintain a high rebound rate under different temperature environments, thereby effectively improving the overall thermal conductivity and rebound ability of the thermal gasket.
[0014] Preferably, the spandex fiber is treated with plasma to obtain modified spandex fiber.
[0015] In a plasma environment, high-energy particles interact with the surface of spandex fibers, causing etching on the fiber surface and increasing the roughness, which is beneficial to enhancing the mechanical bite force between the subsequent slurry and the fiber and improving the interface bonding strength; at the same time, the active particles in the plasma will trigger a series of chemical reactions, introducing active functional groups on the surface of the spandex fibers. These functional groups can chemically bond with the fiber modification liquid and the active ingredients in the slurry, further enhancing the interaction between the components. This enhanced interface bonding and chemical bonding is beneficial to more efficient heat conduction between the fiber and the slurry, reducing thermal resistance and improving the overall thermal conductivity efficiency; the modified spandex fibers form a tighter and more stable structure with other materials. When compressed by external force, the fibers can better cooperate with the slurry to resist deformation, and after the external force disappears, they can recover to their initial state more quickly and completely due to their own good elasticity and firm connection with the surrounding materials, thereby significantly improving the rebound rate of the thermal conductive gasket.
[0016] Preferably, the plasma treatment power is 100-300 W, the gas atmosphere is argon and oxygen, the gas flow rate is 20-30 mL / min, and the treatment time is 4-8 min.
[0017] Argon, as the main plasma-generating gas, can etch the fiber surface through physical bombardment to increase the roughness; oxygen can chemically react with the fiber surface to introduce oxygen-containing functional groups, thereby enhancing the chemical activity of the fiber surface; under such precisely controlled plasma treatment conditions, the spandex fiber surface can form moderate roughness and abundant active functional groups, greatly enhancing its bonding with subsequent coating materials, effectively improving the thermal conductivity of the thermally conductive gasket, and enabling heat to be conducted more quickly between the fiber and other materials; the modified spandex fiber can better support and coordinate the material to return to its original state, thereby meeting the performance requirements for efficient heat dissipation and high elastic recovery of the composite high-rebound thermally conductive gasket, enabling it to have better application performance in fields such as electronic equipment heat dissipation.
[0018] Preferably, the volume ratio of argon and oxygen is (7-8): (2-3).
[0019] In this ratio range, argon is dominant, and the large number of high-energy particles it produces in the plasma state can moderately physically bombard the surface of the spandex fiber, effectively increasing the roughness of the fiber surface, providing more contact sites for subsequent bonding with other materials, and enhancing the mechanical interlocking effect, thereby enhancing the overall structural stability of the thermal pad; an appropriate amount of oxygen participates in the reaction, and the active oxygen species it produces can react with the chemical bonds on the surface of the spandex fiber, introducing a sufficient number of evenly distributed oxygen-containing functional groups, such as hydroxyl and carboxyl groups, which can enhance the chemical bonding between the fiber and coating materials such as hydrogen-containing silicone oil. , improve the interface compatibility between materials, promote heat transfer between different phases, and improve thermal conductivity; on the other hand, after the gasket is compressed and deformed by external force, this chemical bonding can better coordinate the stress distribution of each component, assist the spandex fiber to restore its original shape with its own elasticity, and effectively improve the rebound rate; by precisely controlling the volume ratio of argon and oxygen, the spandex fiber, after plasma treatment, can have good surface roughness to enhance physical bonding, and have rich active functional groups to strengthen chemical bonding, ultimately achieving the synergistic improvement of the thermal conductivity and rebound properties of the composite high-rebound thermal conductive gasket.
[0020] Preferably, the mass fractions of the components in the slurry are 480-520 parts of aluminum oxide, 20-25 parts of vinyl silicone oil, 3-5 parts of hydrogenated silicone oil, 0.1-0.2 parts of catalyst and 0.5-1 parts of inhibitor.
[0021] Alumina, as a key thermal conductive filler, has excellent thermal conductivity. It can build an efficient heat conduction channel inside the gasket, which effectively enhances the overall thermal conductivity of the material, ensures that heat can be quickly diffused, and meets the strict requirements of electronic equipment for heat dissipation; vinyl silicone oil and hydrogen-containing silicone oil work together to effectively wrap the filler particles to prevent them from agglomerating and ensure the uniform dispersion of the filler in the system, thereby maintaining stable and reliable thermal conductivity, and can also undergo cross-linking reactions during the curing process to form a stable and elastic network structure. This unique network structure gives the thermal conductive gasket good flexibility, so that after being compressed by external force, it can quickly return to its initial state with its own strong elastic recovery force, thereby improving the rebound rate; an appropriate amount of catalyst can accelerate the cross-linking reaction process, ensure the formation of a complete cross-linking network within a reasonable processing time, and improve production efficiency and product performance stability; the inhibitor can accurately control the rate of the cross-linking reaction to avoid internal stress concentration or structural defects in the material caused by too fast a reaction, and ensure that the gasket has uniform structure and consistent performance during the molding process.
[0022] Preferably, the catalyst comprises a platinum-vinylsiloxane complex catalyst, and the inhibitor comprises acetylene cyclohexanol.
[0023] The platinum-vinylsiloxane complex catalyst can efficiently catalyze the cross-linking reaction between vinyl silicone oil and hydrogen-containing silicone oil in the slurry system. By coordinating with the silicon-hydrogen bond, the activation energy of the reaction is reduced, so that the cross-linking reaction can proceed rapidly and fully under relatively mild conditions, which helps to enhance the uniformity and regularity of the network structure, so that the thermal conductive gasket has more stable and reliable physical properties after curing, thereby ensuring the stability and consistency of its thermal conductivity and resilience performance; acetylene cyclohexanol is used as an inhibitor, and its molecular structure contains special active groups, which can accurately and efficiently interact with the fast-reacting active sites in the system, effectively control the rate of the cross-linking reaction, avoid stress concentration inside the material due to too fast cross-linking reaction, prevent structural defects such as holes and cracks, and ensure that the gasket has a uniform and dense structure during the molding process; the two work together to accurately control the cross-linking process, so that the synergistic effect between the components can be fully exerted, so that the composite high-rebound thermal conductive gasket has good structural integrity and stability while achieving excellent thermal conductivity and high rebound rate, further improving its reliability and durability in practical applications.
[0024] Preferably, the heating and curing conditions are to increase the temperature to 40-60°C at a rate of 5°C / min, apply a pressure of 0.03-0.05MPa, keep warm for 10-20min, maintain the pressure conditions, increase the temperature to 80°C at a rate of 3°C / min, and keep warm for 50-70min.
[0025] A relatively gentle initial heating rate is adopted, and a certain pressure is applied for preliminary insulation, which enables the components in the slurry to slowly and evenly contact each other under pressure and begin to react, avoiding violent reactions and uneven curing caused by a sharp increase in temperature. The main components such as vinyl silicone oil, hydrogen silicone oil and alumina particles begin to interact with each other, and the cross-linking reaction between the silicone oils is initially started. The alumina particles are gradually closely combined with the silicone oil to form a preliminary stable structural framework; the steps of further increasing the temperature and performing insulation promote the cross-linking reaction to continue in depth, so that the cross-linking network continues to develop and tends to be dense and perfect, enhancing the integrity of the material and the inherent elastic recovery ability, thereby effectively improving the rebound rate; this curing method combining gradual heating and reasonable insulation can cleverly balance the stress distribution inside the material, significantly reduce the accumulation and concentration of internal stress, and reduce the generation of defects such as microcracks and pores caused by stress problems, effectively ensuring the structural integrity and uniformity of the thermal pad, thereby improving the thermal conductivity and rebound ability of the thermal pad.
[0026] In summary, the present application includes at least one of the following beneficial technical effects: 1. The characteristics of elastic fabric are used to achieve high rebound effect. When subjected to pressure in the Z direction, the prefabricated fabric will undergo elastic deformation. Once the external force is removed, it can quickly return to its original state, greatly reducing the dependence on resin; under the premise of ensuring the same rebound level, the resin weight ratio can be significantly reduced, thereby greatly increasing the powder filling rate of the high rebound thermal pad, thereby improving thermal conductivity and rebound ability and reducing costs.
[0027] 2. Hydrogenated silicone oil has active silicon-hydrogen bonds, which can react chemically with the active groups on the surface of elastic fabric fibers to form chemical bonds, thereby chemically modifying the fiber surface and enhancing the compatibility and adhesion between the fiber and the subsequent coating slurry; naphtha can help the hydrogenated silicone oil to better disperse and penetrate into the internal structure of the fiber, so that the hydrogenated silicone oil is evenly distributed on the fiber surface to ensure the consistency of the modification effect; this uniform and effective modification allows the fiber to better cooperate with the slurry in the subsequent processing process. In terms of improving the thermal conductivity of the thermal conductive gasket, the modified fiber can conduct heat more effectively and promote the transfer of heat inside the gasket; due to the close combination of the fiber and the slurry and the optimization of the fiber's own performance, when the gasket is compressed by external force, the fiber can more effectively support and assist the material to return to its original shape, thereby significantly improving the comprehensive performance of the composite high-resilience thermal conductive gasket, so that it can better meet the needs of heat dissipation and elastic recovery in practical applications.
[0028] 3. Argon is dominant, and the large number of high-energy particles it produces in the plasma state can moderately physically bombard the surface of the spandex fiber, effectively increasing the roughness of the fiber surface, providing more contact sites for subsequent bonding with other materials, and enhancing the mechanical interlocking effect, thereby enhancing the overall structural stability of the thermal conductive gasket; an appropriate amount of oxygen participates in the reaction, and the active oxygen species it produces can react with the chemical bonds on the surface of the spandex fiber, introducing a sufficient number of evenly distributed oxygen-containing functional groups, such as hydroxyl and carboxyl groups. These functional groups can, on the one hand, enhance the chemical bonding between the fiber and coating materials such as hydrogen-containing silicone oil, thereby improving The interfacial compatibility between materials promotes the transfer of heat between different phases and improves the thermal conductivity efficiency. On the other hand, after the gasket is compressed and deformed by external force, this chemical bonding can better coordinate the stress distribution of each component, assisting the spandex fiber to recover its original shape with its own elasticity, and effectively improve the rebound rate. By precisely controlling the volume ratio of argon and oxygen, the spandex fiber, after plasma treatment, can have good surface roughness to enhance physical bonding, and have rich active functional groups to strengthen chemical bonding, ultimately achieving a synergistic improvement in thermal conductivity and rebound performance of the composite high-rebound thermally conductive gasket. DETAILED DESCRIPTION
[0029] The present application discloses a method for manufacturing a composite high-resilience thermally conductive gasket. The raw materials used in the present application can be obtained from commercially available raw materials unless otherwise specified. The present application is further described in detail below in conjunction with the embodiments: Description of raw materials: The elastic fabric fiber in the embodiment of the present application is spandex fiber, hydrogen-containing silicone oil (CAS No.: 63148-57-2), the alumina is a spherical alumina compound powder, the compound powder contains spherical alumina with three particle sizes, and the particle sizes are 3±0.5μm, 10±2um, and 40±3um, respectively. The weight ratio of the three powders in the compound powder is 15:30:55, vinyl silicone oil (CAS No.: 26710-23-6), the platinum-vinylsiloxane complex catalyst is divinyltetramethyldisiloxane platinum complex (CAS: 68478-92-2), and the inhibitor is acetylene cyclohexanol (CAS No.: 78-27-3).
[0030] Example 1 (1) evenly dispersing hydrogen-containing silicone oil in naphtha to obtain a fiber modification liquid, wherein the hydrogen-containing silicone oil accounts for 3% of the total mass of the fiber modification liquid; transferring the fiber modification liquid into a coating line tank, and evenly coating the elastic fabric fiber at a line speed of 1 m / min to wet the elastic fabric fiber to obtain a modified fabric fiber; (2) drying the modified fabric fiber by hot air at 80° C. and cutting the modified fabric fiber into a size of 500×500 mm to obtain pretreated fabric fiber; (4) 500 g of spherical alumina, 20 g of vinyl silicone oil, 3 g of hydrogenated silicone oil, 0.1 g of catalyst and 0.5 g of inhibitor were mixed, stirred at 30 rpm for 1 h in a planetary mixer, and vacuum degassed at -0.1 MPa for 15 min to obtain a slurry; (5) pre-tensioning the pretreated fabric fiber to make the surface wrinkle-free to obtain a pre-tensioned fabric fiber, coating the slurry on one surface of the pre-tensioned fabric fiber, and heating and curing, coating the slurry on the other surface of the pre-tensioned fabric fiber, and heating and curing to obtain a semi-finished product, the heating and curing conditions are: heating to 40°C at a rate of 5°C / min, applying a pressure of 0.05MPa, keeping the temperature for 20min, maintaining the pressure, heating to 80°C at a heating rate of 3°C / min, and keeping the temperature for 50min; (5) removing excess fabric from the tensioning edge of the semi-finished product to obtain a composite high-resilience thermal conductive gasket.
[0031] Example 2 (1) evenly dispersing hydrogen-containing silicone oil in naphtha to obtain a fiber modification liquid, wherein the hydrogen-containing silicone oil accounts for 8% of the total mass of the fiber modification liquid; transferring the fiber modification liquid into a coating line tank, and evenly coating the elastic fabric fiber at a line speed of 1 m / min to wet the elastic fabric fiber to obtain a modified fabric fiber; (2) drying the modified fabric fiber by hot air at 80° C. and cutting the modified fabric fiber into a size of 500×500 mm to obtain pretreated fabric fiber; (4) 520 g of spherical alumina, 25 g of vinyl silicone oil, 5 g of hydrogenated silicone oil, 0.2 g of catalyst and 1 g of inhibitor were mixed, stirred at 30 rpm for 1 h in a planetary mixer, and vacuum degassed at -0.1 MPa for 15 min to obtain a slurry; (5) pre-tensioning the pretreated fabric fiber to make the surface wrinkle-free to obtain a pre-tensioned fabric fiber, coating the slurry on one surface of the pre-tensioned fabric fiber, and heating and curing, coating the slurry on the other surface of the pre-tensioned fabric fiber, and heating and curing to obtain a semi-finished product, the heating and curing conditions are: heating to 60°C at a rate of 5°C / min, applying a pressure of 0.03MPa, keeping the temperature for 10min, maintaining the pressure, heating to 80°C at a heating rate of 3°C / min, and keeping the temperature for 70min; (5) removing excess fabric from the tensioning edge of the semi-finished product to obtain a composite high-resilience thermal conductive gasket.
[0032] Example 3 (1) evenly dispersing hydrogen-containing silicone oil in naphtha to obtain a fiber modification liquid, wherein the hydrogen-containing silicone oil accounts for 5.5% of the total mass of the fiber modification liquid; transferring the fiber modification liquid into a coating line tank, and evenly coating the elastic fabric fiber at a line speed of 1 m / min to wet the elastic fabric fiber to obtain a modified fabric fiber; (2) drying the modified fabric fiber by hot air at 80° C. and cutting the modified fabric fiber into a size of 500×500 mm to obtain pretreated fabric fiber; (4) 480 g of spherical alumina, 22.5 g of vinyl silicone oil, 4 g of hydrogenated silicone oil, 0.15 g of catalyst and 0.75 g of inhibitor were mixed, stirred at 30 rpm in a planetary mixer for 1 h, and vacuum degassed at -0.1 MPa for 15 min to obtain a slurry; (5) pre-tensioning the pretreated fabric fiber to make the surface wrinkle-free to obtain a pre-tensioned fabric fiber, coating the slurry on one surface of the pre-tensioned fabric fiber, and heating and curing, coating the slurry on the other surface of the pre-tensioned fabric fiber, and heating and curing to obtain a semi-finished product, the heating and curing conditions are: heating to 50° C. at a rate of 5° C. / min, applying a pressure of 0.04 MPa, keeping the temperature for 15 minutes, maintaining the pressure, heating to 80° C. at a heating rate of 3° C. / min, and keeping the temperature for 60 minutes; (5) removing excess fabric from the tensioning edge of the semi-finished product to obtain a composite high-resilience thermal conductive gasket.
[0033] Example 4 Example 4 is based on Example 3. The only difference between Example 4 and Example 3 is that in Example 4, the hydrogen-containing silicone oil accounts for 1% of the total mass of the fiber modification liquid.
[0034] Example 5 Example 5 is based on Example 3. The only difference between Example 5 and Example 3 is that in Example 5, the hydrogen-containing silicone oil accounts for 10% of the total mass of the fiber modification liquid.
[0035] Preparation Example 1 Preparation of modified spandex fiber The spandex fiber was ultrasonically washed with anhydrous ethanol and dried at room temperature to obtain pretreated spandex fiber; the power of the plasma treatment equipment was set to 100 W, a mixed gas of argon and oxygen was used as the working gas, the gas flow rate was set to 30 mL / min, the volume ratio of argon and oxygen was 7:3, the treatment time was 8 min, and modified spandex fiber was obtained.
[0036] Preparation Example 2 Preparation Example 2 is based on Preparation Example 1. The only difference between Preparation Example 2 and Preparation Example 1 is that in Preparation Example 2, the plasma treatment power is 300 W, the volume ratio of argon and oxygen is 8:2, the gas flow rate is 20 mL / min, and the treatment time is 4 min.
[0037] Preparation Example 3 Preparation Example 3 is based on Preparation Example 1. The only difference between Preparation Example 3 and Preparation Example 1 is that in Preparation Example 3, the plasma treatment power is 200 W, the volume ratio of argon and oxygen is 7.5:2.5, the gas flow rate is 25 mL / min, and the treatment time is 6 min.
[0038] Preparation Example 4 Preparation Example 4 is based on Preparation Example 1. The only difference between Preparation Example 4 and Preparation Example 1 is that in Preparation Example 4, the plasma treatment power is 80 W, the volume ratio of argon and oxygen is 6:4, the gas flow rate is 35 mL / min, and the treatment time is 10 min.
[0039] Preparation Example 5 Preparation Example 5 is based on Preparation Example 1. The only difference between Preparation Example 5 and Preparation Example 1 is that in Preparation Example 5, the plasma treatment power is 350 W, the volume ratio of argon and oxygen is 8.5:1.5, the gas flow rate is 15 mL / min, and the treatment time is 2 min.
[0040] Example 6 Example 6 is based on Example 3. The only difference between Example 6 and Example 3 is that the elastic fabric fiber in Example 6 is treated with plasma, and the elastic fabric fiber is the modified spandex fiber prepared in Preparation Example 1.
[0041] Example 7 Example 7 is based on Example 3. The only difference between Example 7 and Example 3 is that in Example 7, the elastic fabric fiber is treated with plasma, and the elastic fabric fiber is the modified spandex fiber prepared in Preparation Example 2.
[0042] Example 8 Example 8 is based on Example 3. The only difference between Example 8 and Example 3 is that the elastic fabric fiber in Example 8 is treated with plasma, and the elastic fabric fiber is the modified spandex fiber prepared in Preparation Example 3.
[0043] Example 9 Example 9 is based on Example 3. The only difference between Example 9 and Example 3 is that the elastic fabric fiber in Example 9 is treated with plasma, and the elastic fabric fiber is the modified spandex fiber prepared in Preparation Example 4.
[0044] Example 10 Example 10 is based on Example 3. The only difference between Example 10 and Example 3 is that in Example 10, the elastic fabric fiber is subjected to plasma treatment, and the elastic fabric fiber is the modified spandex fiber prepared in Preparation Example 5.
[0045] Embodiment 11 Example 11 is based on Example 3. The only difference between Example 11 and Example 3 is that the heating and curing conditions in Example 11 are heating to 50°C at a rate of 5°C / min, keeping warm for 15 minutes, heating to 80°C at a rate of 3°C / min, and keeping warm for 60 minutes.
[0046] Example 12 Example 12 is based on Example 3. The only difference between Example 12 and Example 3 is that the heating and curing conditions in Example 12 are to increase the temperature to 80°C at a heating rate of 3°C / min, apply a pressure of 0.4 MPa, and keep warm for 60 minutes.
[0047] Comparative Example 1 Comparative Example 1 is based on Example 3, and the only difference between Comparative Example 1 and Example 3 is that the elastic fabric fibers in Comparative Example 1 are not treated with the fiber modification liquid.
[0048] Performance testing (1) Select "ASTM D 5470-2017 Standard Test Method for Thermal Conductivity of Thermally Conductive Electrical Insulating Materials" as the standard, and use the DRL-III series thermal conductivity tester to test the thermal conductivity of the sample. Each sample is tested three times, and the average value is taken after measurement. The results are recorded in Table 1.
[0049] (2) Select "GB / T12622-2008 Test method for compression rate and rebound rate of gaskets for pipe flanges" as the standard, apply pressure to a sample with a thickness of 1 mm, stop loading pressure after compression of 30%, maintain pressure for 30 seconds and then release pressure. After the sample rebounds and stabilizes, record the thickness at this time and calculate the rebound rate of the sample. Prepare three samples for each sample, take the average value after measurement, and record the results in Table 1.
[0050] (3) ASTM D 2240-2015 was selected as the standard, and the hardness of the sample was tested using a Shore OO hardness tester. Each sample was tested three times, and the average value was taken after measurement. The results are recorded in Table 1.
[0051] Table 1 Test results of thermal conductivity, rebound ability and hardness of composite high-rebound thermal conductive gasket It can be seen from Table 1 that the thermal conductivity of Examples 1-3 is greater than 6.22w / (m·k), the rebound rate is greater than 98.7%, and the hardness is less than 56.6, which shows that the thermal conductive gasket prepared in this application has good thermal conductivity and rebound performance, and has low hardness.
[0052] It can be seen from Table 1 that the only difference between Examples 4 and 5 and Example 3 is that in Example 4, the hydrogen-containing silicone oil accounts for 1% of the total mass of the fiber modification liquid, and in Example 5, the hydrogen-containing silicone oil accounts for 10% of the total mass of the fiber modification liquid. Compared with Example 3, the thermal conductivity and resilience of the thermally conductive gasket in Examples 4 and 5 are reduced; this is because the amount of hydrogen-containing silicone oil is changed. Too much hydrogen-containing silicone oil will excessively consume the active groups on the fiber surface, causing damage to the fiber structure and uneven modification effect; too little hydrogen-containing silicone oil will affect the modification effect, resulting in insufficient modification effect, reduced compatibility and bonding force, and thus reduced performance of the thermally conductive gasket.
[0053] It can be seen from Table 1 that the only difference between Example 6-10 and Example 3 is that in Example 6-10, the elastic fabric fiber is modified and modified spandex fiber is used. Compared with Example 3, the thermal conductivity and resilience of Example 6-10 are improved; this is because the plasma treatment increases the active groups on the surface of the spandex fiber, increases the roughness, and increases the compatibility and bonding force, thereby improving the performance; Examples 9 and 10 were not treated within the specified range, and the performance was slightly reduced.
[0054] As can be seen from Table 1, the only difference between Examples 11 and 12 and Example 3 is that: in Example 11, no pressurization treatment is performed during heating and curing, and in Example 12, no segmented heating treatment is performed. Compared with Example 3, Examples 11 and 12 have reduced thermal conductivity and resilience. This is because not performing pressurization or segmented heating treatment will affect the uniformity and consistency of the cross-linking reaction, thereby affecting the cross-linking effect, thereby reducing the thermal conductivity and resilience.
[0055] It can be seen from Table 1 that the only difference between Comparative Example 1 and Example 3 is that: in Comparative Example 1, no fiber modification liquid is used for modification treatment. Compared with Example 3, the thermal conductivity and resilience of Comparative Example 1 are reduced; this is because the compatibility and adhesion of the spandex fiber are reduced due to the lack of modification treatment with hydrogenated silicone oil, and the synergistic effect between the components is weakened, thereby reducing the thermal conductivity and resilience.
[0056] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for manufacturing a composite high-resilience thermally conductive gasket, characterized in that: The following steps are involved: (1) preparing a fiber modification liquid, coating the fiber modification liquid on elastic fabric fibers, and obtaining modified fabric fibers after impregnation; (2) drying the modified fabric fibers and cutting them to obtain pretreated fabric fibers; (4) mixing alumina, vinyl silicone oil, hydrogen-containing silicone oil, a catalyst and an inhibitor to obtain a slurry; (5) pre-tensioning the pretreated fabric fiber to make the surface wrinkle-free to obtain pre-tensioned fabric fiber, coating the slurry on one surface of the pre-tensioned fabric fiber, heating and curing, coating the slurry on the other surface of the pre-tensioned fabric fiber, heating and curing to obtain a semi-finished product; (5) Remove excess fabric from the tensioning edge of the semi-finished product to obtain a composite high-resilience thermal conductive gasket.
2. The method for manufacturing a composite high-resilience thermally conductive gasket according to claim 1, characterized in that: The fiber modification liquid comprises hydrogen-containing silicone oil and naphtha.
3. The method for manufacturing a composite high-resilience thermally conductive gasket according to claim 2, characterized in that: The hydrogen-containing silicone oil accounts for 3-8% of the total mass of the fiber modification liquid.
4. The method for manufacturing a composite high-resilience thermally conductive gasket according to claim 1, characterized in that: The elastic fabric fibers include spandex fibers.
5. The method for manufacturing a composite high-resilience thermally conductive gasket according to claim 4, characterized in that: The spandex fiber is treated by plasma to obtain modified spandex fiber.
6. The method for manufacturing a composite high-resilience thermally conductive gasket according to claim 5, characterized in that: The plasma treatment power is 100-300W, the gas atmosphere is argon and oxygen, the gas flow rate is 20-30mL / min, and the treatment time is 4-8min.
7. The method for manufacturing a composite high-resilience thermally conductive gasket according to claim 6, characterized in that: The volume ratio of argon and oxygen is (7-8): (2-3).
8. The method for manufacturing a composite high-resilience thermally conductive gasket according to claim 1, characterized in that: The mass proportions of the components in the slurry are 480-520 parts of aluminum oxide, 20-25 parts of vinyl silicone oil, 3-5 parts of hydrogen-containing silicone oil, 0.1-0.2 parts of catalyst and 0.5-1 parts of inhibitor.
9. The method for manufacturing a composite high-resilience thermally conductive gasket according to claim 8, characterized in that: The catalyst includes a platinum-vinylsiloxane complex catalyst, and the inhibitor includes acetylene cyclohexanol.
10. The method for manufacturing a composite high-resilience thermally conductive gasket according to claim 1, characterized in that: The heating and curing conditions are: heating to 40-60°C at a rate of 5°C / min, applying a pressure of 0.03-0.05MPa, keeping warm for 10-20min, maintaining the pressure conditions, heating to 80°C at a rate of 3°C / min, and keeping warm for 50-70min.